Intersubjective Perspectives on Intersexuality and Spectator Identification in Puenzo’s XXY - Castillo, Anna (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2023)
Intersexuality is underrepresented in film, yet in key sequences in XXY, perspectival patterns kindle attentiveness to intersex subjectivity by focalizing the experiences of a secondary, non-intersex identified character. What is gained by rendering intersexuality from the vantage point of one who has yet to experience it? This article argues that the film’s visual and aural grammar queers intersexuality itself, undoing dichotomic borders between “intersex” and “non-intersex” by making intersexuality a relational rather than purely anatomical quality. This intersubjective rendering of intersexuality facilitates alternative pathways for audience identification with intersexuality, a topic yet unexplored in the film’s robust body of criticism.